Anti-Tumor Effect of Orally Administered Spinach Glycolipid Fraction on Implanted Cancer Cells, Colon-26, in Mice - Maeda, Naoki; Kokai, Yasuo; Ohtani, Seiji; Sahara, Hiroeki; Kumamoto-Yonezawa, Yuko; Kuriyama, Isoko; Hada, Takahiko; Sato, Noriyuki; Yoshida, Hiromi; Mizushina, Yoshiyuki (Lipids, 2008)
We succeeded in purifying a major glycolipid fraction from a green vegetable, spinach. This fraction consists mainly of three glycolipids: monogalactosyl diacylglycerol (MGDG), digalactosyl diacylglycerol (DGDG), and sulfoquinovosyl diacylglycerol (SQDG). In a previous study, we found that the glycolipid fraction inhibited DNA polymerase activity, cancer cell growth and tumor growth with subcutaneous injection. We aimed to clarify oral administration of the glycolipid fraction, suppressing colon adenocarcinoma (colon-26) tumor growth in mice. A tumor graft study showed that oral administration of 20 mg/kg glycolipid fraction for 2 weeks induced a 56.1% decrease in the solid tumor volume (P < 0.05) without any side-effects, such as loss of body weight or major organ failure, in mice. The glycolipid fraction induced the suppression of colon-26 tumor growth with inhibition of angiogenesis and the expression of cell proliferation marker proteins such as Ki-67, proliferating cell nuclear antigen (PCNA), and Cyclin E in the tumor tissue. These results suggest that the orally administered glycolipid fraction from spinach could suppress colon tumor growth in mice by inhibiting the activities of neovascularization and cancer cellular proliferation in tumor tissue.